Missing relationship of moyamoya and persistent primitive artery in Europeans. Another distinctive feature or artifact? - Wenz, Holger; Förster, Alex; Kerl, Hans Ulrich; Groden, Christoph; Scharf, Johann (Surgical and radiologic anatomy. [Englische Ausgabe], 2015)
PurposePrevious studies found higher incidence of persistent primitive arteries in Asian moyamoya (MM) patients than in the general population, which was thought to be a characteristic trait of the MM entity in general. We analyzed incidence of persistent primitive arteries and demographics of patients with European MM treated in one single center. First, we compared our large dataset to existing literature and second, we raised the question whether European MM demonstrates similar high prevalence of persistent primitive arteries as it was previously presented within Asian MM.MethodsAll European MM on whom revascularization surgery was performed from 1999 to 2013 were included. Demographics and associated diseases were obtained by retrospective chart review. Two independent readers evaluated 122 MM angiograms to determine the occurrence of persistent primitive arteries as well as the Suzuki score.ResultsWe identified 112 cases with MM disease, 10 with MM syndrome. Mean age at time of diagnosis was 38.2 (range 6-64 years); a peak incidence in early childhood was not observed. Ninety (73.8 %) were women, associated systemic diseases were found in four patients. Seven cases (5.7 %) presented with unilaterally affected vessels. The majority of patients (71; 58.2 %) were graded Suzuki Score 3. One 14-year-old boy with moyamoya presented with a primitive trigeminal artery (0.89 %).ConclusionsWe did not find a bimodal age distribution, but only a second peak during adulthood. Unlike previous studies on Asian moyamoya patients, our collective does not exhibit a higher prevalence of persistent primitive arteries than the normal population.